Proceedings of Fifth IEEE International Conference on Automatic Face Gesture Recognition
DOI: 10.1109/afgr.2002.1004186
|View full text |Cite
|
Sign up to set email alerts
|

Visual prosody: facial movements accompanying speech

Abstract: As we articulate speech, we usually move the head and exhibit various facial expressions. This visual aspect of speech aids understanding and helps communicating additional information, such as the speaker's mood. In this paper we analyze quantitatively head and facial movements that accompany speech and investigate how they relate to the text's prosodic structure. We recorded several hours of speech and measured the locations of the speakers' main facial features as well as their head poses. The text was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
1
1

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 7 publications
8
82
1
1
Order By: Relevance
“…The prosodic word carries both prosodic structure and semantic meaning in Chinese spoken language. Early study has found that head movement are strongly correlated with the prosodic structure of the text [18]. In our data, we have observed the head moves periodically and is nearly synchronous with the segmentation of prosodic word.…”
Section: Head Motion Features Extractionsupporting
confidence: 62%
See 3 more Smart Citations
“…The prosodic word carries both prosodic structure and semantic meaning in Chinese spoken language. Early study has found that head movement are strongly correlated with the prosodic structure of the text [18]. In our data, we have observed the head moves periodically and is nearly synchronous with the segmentation of prosodic word.…”
Section: Head Motion Features Extractionsupporting
confidence: 62%
“…The first assumption has been validated in Section 3.1. The second assumption of head shake motion pattern during speech has also been observed in previous study [18,20]. A sinusoidal function is proposed to generate head motion sequence within prosodic word based on the above assumptions.…”
Section: Head Motion Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…These studies take the position of the accented syllables as the key prosodic landmark with which gesture movements align, but they do not take into account intonational phrase boundaries. In general, they found a similar temporal alignment pattern as had been shown for hand gestures: accented syllables are the anchoring point in speech for the most prominent part of a head movement, the gesture apex (defined as the specific point in time when the head changes its direction in the vertical or lateral movement) (Alexanderson et al, 2013;Ambrazaitis et al, 2015;Fernandez-Baena et al, 2014;Goldenberg et al, 2014;Graf et al, 2002;Hadar et al, 1983;Ishi et al, 2014;Kim et al, 2014). However, these studies also reported variability in this alignment pattern.…”
Section: Introductionmentioning
confidence: 74%